2018
DOI: 10.1590/1678-457x.36416
|View full text |Cite
|
Sign up to set email alerts
|

Peel and pulp of baru (Dipteryx Alata Vog.) provide high fiber, phenolic content and antioxidant capacity

Abstract: Baru (Dipteryx alata Vog.) is a native fruit of the Brazilian Savannah that can be used in the food industry and may contribute to the economy of the Brazilian Midwest. The proximate composition, the phenolic content and the antioxidant capacity of the peel, pulp and raw and roasted baru almond were examined and compared. Peel showed higher concentrations of dietary fibers (24.1 g/100 g) followed by pulp and roasted almond (18 g/100 g and 16 g/100 g, respectively), and raw almond (12.0 g/100 g). However, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
2
18
1
2
Order By: Relevance
“…This packaging is permeable to light, and to preserve the phenolic content, transparent packaging can be used. Siqueira et al (2012) found 154.6 mg 100g -1 of total phenols in baru almonds, a value lower than that found in this study during storage for up to 60 days, but over time, values came close, while Santiago et al (2018) obtained higher values 728 mg GAE100g -1 ).…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…This packaging is permeable to light, and to preserve the phenolic content, transparent packaging can be used. Siqueira et al (2012) found 154.6 mg 100g -1 of total phenols in baru almonds, a value lower than that found in this study during storage for up to 60 days, but over time, values came close, while Santiago et al (2018) obtained higher values 728 mg GAE100g -1 ).…”
Section: Resultscontrasting
confidence: 67%
“…Almonds have high protein (22.9 100g -1 ) and lipid (40.6g 100g -1 ) content (Santiago et al, 2018) with predominance of oleic (omega-9) and linoleic (omega-3) fatty acids (Siqueira et al, 2016), in addition to high content of phenolic compounds with antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…A mesma tendência pôde ser verificada neste trabalho, pois, a 80 °C houve redução dos flavonoides. Este decréscimo é devido à facilidade de degradação desses compostos em temperaturas elevadas, indicando que o método de secagem deve considerar temperaturas de até 70 ºC para manter os melhores níveis de flavonoides, que são constituintes considerados bioativos e com capacidade de sequestrar radicais livres (Santiago et al, 2018).…”
Section: Resultsunclassified
“…As variações de temperaturas de secagem entre 50 e 80 ºC não foram suficientes para degradar os compostos fenólicos. Santiago et al (2018) analisaram a influência do tratamento térmico na quantidade de compostos fenólicos e capacidade antioxidante do baru presentes na polpa e amêndoas cruas e torradas. Os resultados expressaram quantidades superiores de fenólicos e maior capacidade antioxidante na amêndoa crua quando comparada com a amêndoa torrada a 140 ºC.…”
Section: Resultsunclassified
“…This edible seed is popularly known as baru almond (or baru nut) and consumed roasted, whole, or without skin (Sousa et al, 2011). Baru almond is rich in nutrients, such as monounsaturated fatty acids, dietary fiber, vitamin E, and zinc, and the whole baru almond (with skin) is a source of phenolic compounds and has a high antioxidant capacity (Fernandes et al, 2015;Santiago et al, 2018) compared to other oilseeds (Rodríguez-Bencomo et al, 2015;Ozer, 2017). However, the seed without skin contains significantly lower phenolic compounds content and antioxidant capacity (Lemos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%